A Case of ALERD Masquerading as Paracetamol Poisoning - Kalyanshettar, Siddarameshwar S; Patil, Shankargouda V; VJ, Prakash; Mahaldar, Asif; Teggi, Prashant (Journal of Nepal Paediatric Society, 2020)
ALERD (Acute leukoencephalopathy with restricted diffusion) is a clinico – radiological diagnosis. Many novel causes of acute encephalopathy are emerging in children. MRI plays an important role in the diagnosis and management of such children. Many infectious and non-infectious conditions and poisonings are known to precipitate acute leukoencephalopathy. A commonly used drug like paracetamol ingested in large quantities is known to cause varied effects. We describe one such child who presented to us with paracetamol poisoning and developed acute leukoencephalopathy. He was later found to have restricted diffusion on magnetic resonance imaging.